Demographic synthesis for global tree species conservation. (June 2023) - Ohse, Bettina; Compagnoni, Aldo; Farrior, Caroline E.; McMahon, Sean M.; Salguero-Gómez, Roberto; Rüger, Nadja; Knight, Tiffany M.
Highlights: Almost one-third of globally known tree species are threatened with extinction, calling for a better understanding of the vulnerability of tree species to different threats. Quantifying changes in vital rates (e.g., survival, growth, or reproduction) in response to threats has helped assess which of these rates of a given species are the most critical to the population response to a threat. To more generally understand which types of tree species, based on their life-history strategies, are more vulnerable compared with others, comparative analyses of demographic data across the phylogenetic 'Tree of trees' and biomes are needed. Demographic model parameterization for comparative analyses hinges on improving coverage of data on mortality and recruitment (e.g., through distributed observation networks). Systematic modeling would greatly help explore which life-history strategies of species are the best predictors of their vulnerability to different threats, prioritize data collection, and potentially suggest management alternatives. Abstract: Conserving the tree species of the world requires syntheses on which tree species are most vulnerable to pressing threats, such as climate change, invasive pests and pathogens, or selective logging. Here, we review the population and forest dynamics models that, when parameterized with data from population studies, forest inventories, or tree rings, have been used for identifying life-history strategies of species and threat-related changes in population demography and dynamics. The available evidence suggests that slow-growing and/or long-lived species are the most vulnerable. However, a lack of comparative, multi-species studies still challenges more precise predictions of the vulnerability of tree species to threats. Improving data coverage for mortality and recruitment, and accounting for interactions among threats, would greatly advance vulnerability assessments for conservation prioritizations of trees worldwide.